Reformacja na Śląsku Cieszyńskim w kontekście miejscowej sytuacji językowej - Raclavská, Jana; Bogoczová, Irena; Muryc, Jiří (Slavia Centralis, 2020)
The present article Reformation in the Teschen Silesian Region in the Context of Local Language Situation describes a district stretching over an area of 2,282 km2 that originated in 1290 at the intersection of at least two Slavic ethnic groups, cultures and languages. Formerly, until the end of World War I or even until July 1920, this area used to form a whole with its cultural, administrative and social centre – the town of Cieszyn/Teschen. Afterwards, both the whole area and the town of Cieszyn were divided into two parts – Czech and Polish. This primarily Slavic territory was subject to German colonization from the 13th Century and a large number of Jewish inhabitants used to live there. The author notes some historical moments related to the specific development of the Protestant Church in the Teschen Silesia region as well as to the general political and social development of this region.
Keywords: Teschen (Cieszyn) Silesia; the Evangelical Church; Polish Language; Jan Muthmann; Samuel Zasadius